Immunophenotyping Reveals Longitudinal Changes in Circulating Immune Cells During Radium-223 Therapy in Patients With Metastatic Castration-Resistant Prostate Cancer - Creemers, Jeroen H. A.; van der Doelen, Maarten J.; van Wilpe, Sandra; Hermsen, Rick; Duiveman-de Boer, Tjitske; Somford, Diederik M.; Janssen, Marcel J. R.; Sedelaar, J. P. Michiel; Mehra, Niven; Textor, Johannes; Westdorp, Harm (Frontiers in Oncology, 2021)
Background Radium-223 improves overall survival (OS) in men with bone metastatic castration-resistant prostate cancer (mCRPC). While the exact mechanism behind this survival benefit remains unclear, radium-induced immunological mechanisms might contribute to the OS advantage. We performed a comprehensive evaluation of the immunological changes in mCRPC patients by phenotyping the peripheral blood mononuclear cells (PBMCs) during radium-223 therapy. Materials and Methods In this prospective, single-arm, exploratory study, PBMCs of 30 mCRPC patients were collected before, during, and after treatment with radium-223. Lymphocyte and monocyte counts were analyzed to get insight into general immune cell trends. Next, we analyzed changes in T cell subsets, myeloid-derived suppressor cells (MDSCs), and immune checkpoint expression using linear regression models. Per subset, the 6-month change (% of baseline) was determined. Bootstrapped 95% confidence intervals were used to measure the degree of uncertainty of our findings. Results We observed a substantial decrease in absolute lymphocyte counts (-0.12 * 10^9 cells/L per injection, 95% CI: -0.143 - -0.102). Simultaneously, an increase was observed in the proportion of T cells that expressed costimulatory (ICOS) or inhibitory (TIM-3, PD-L1, and PD-1) checkpoint molecules. Moreover, the fraction of two immunosuppressive subsets – the regulatory T cells and the monocytic MDSCs – increased throughout treatment. These findings were not more pronounced in patients with an alkaline phosphatase response during therapy. Conclusion Immune cell subsets in patients with mCRPC changed during radium-223 therapy, which warrants further research into the possible immunological consequences of these changes.